2012
DOI: 10.1007/s12237-012-9573-0
|View full text |Cite
|
Sign up to set email alerts
|

Stock Origins of Subadult and Adult Atlantic Sturgeon, Acipenser oxyrinchus, in a Non-natal Estuary, Long Island Sound

Abstract: The anadromous acipenserid Atlantic sturgeon Acipenser oxyrinchus was listed in 2012 under the U.S. Endangered Species Act as having four endangered and one threatened distinct population segment (DPS) in American waters. Anthropogenic activities outside of natal estuaries, particularly bycatch, may hinder the abilities of some populations to rebuild. Most Atlantic sturgeon are residential for their first 2-6 years within their natal estuaries, whereas older subadults and adults may migrate to nonnatal estuari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 23 publications
1
52
1
Order By: Relevance
“…Given the overlapping marine distributions and shared threats among populations and DPSs, the pooled estimate of adult survival should be useful for large-scale recovery planning (Dunton et al 2012;Waldman et al 2013;Wirgin et al 2015aWirgin et al , 2015b. The survival estimate for the ACE basin is probably low, as nine fish that were not detected during the final study FIGURE 2.…”
Section: Atlantic Sturgeon Survival In Four River Basinsmentioning
confidence: 99%
“…Given the overlapping marine distributions and shared threats among populations and DPSs, the pooled estimate of adult survival should be useful for large-scale recovery planning (Dunton et al 2012;Waldman et al 2013;Wirgin et al 2015aWirgin et al , 2015b. The survival estimate for the ACE basin is probably low, as nine fish that were not detected during the final study FIGURE 2.…”
Section: Atlantic Sturgeon Survival In Four River Basinsmentioning
confidence: 99%
“…We quantitatively compared the diversity of source reference populations to the Delaware coast collection to that in collections that we previously made from the Bay of Fundy and Long Island Sound (Waldman et al 2013). As expected, we found that variation of the number of reference populations contributing to the Delaware coast collection expressed as bits was significantly greater (P < 0.001) than for the Bay of Fundy or Long Island Sound collections (Delaware coast D 2.53 bits, Long Island Sound D 1.83 bits, and Bay of Fundy D 1.14 bits).…”
Section: Resultsmentioning
confidence: 99%
“…These diploid markers included LS19, LS39, LS54, and LS68 (May et al 1997); Aox23 and AoxD45 (King et al 2001); and Aox44, AoxD165, AoxD170, AoxD188, and AoxD24 (Henderson-Arzapalo and King 2002). These loci were selected because they could be reliably scored, are unlinked, and in previous studies were effective in distinguishing reference specimens from spawning populations (King et al 2001;Wirgin et al 2012;Waldman et al 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that the loss of genetic diversity may result in inbreeding depression leading to fitness decline often manifested by decrease of growth rate (Borrell et al, 2011 and references therein). Genetic polymorphism and kinship can be easily measured using microsatellite loci that are commonly used as markers in fish restitution and conservation programs including sturgeons (Panagiotopoulou et al, 2012;Waldman et al, 2013;O'Leary, Dunton, King, Frisk & Chapman, 2014;Popović et al, 2014 sturgeon (Acipenser oxyrinchus) breeding is to define causes of large variation in sizes of individuals from the same cohort. Atlantic sturgeon, in contrast to other sturgeon species commonly breed in aquaculture, is difficult to rear, due to specific nutritional requirements and high mortality of larvae and juveniles (Piotrowska, Szczepkowska, KozƂowski, Wundrelich & Szczepkowski, 2013).…”
Section: Introductionmentioning
confidence: 99%